Isolation and Identification of microbes (Fungi and Bacillus species) From Soil and Evaluation of Their Antimicrobial Properties. (Journal of Medical Sciences, 2022)
Five species of bacteria were isolated from different areas from the faculty science soil in addition to four species of fungi and they were tested for the production of the antibacterial substances. The bacterial species were identified by the microscopic examination and the standard biochemical tests. The bacterial isolates were diagnosed as Bacillus spp and were classified as : Bacillus megaterium, Bacillus. licheniformis, Bacillus firmus, Bacillus pumilus, and Bacillus sphaericus while the fungal species, some of them were pre-defined in previous study included: Aspergillus terrrus, Aspergillus niger ,Penicillium chrysogenum and in this study only Fusarium solani was  isolated from the studied area. The antimicrobial activity of the isolated bacteria and fungi was tested against the pathogenic bacteria included: Staphylococcus aureus, Pseudomonas aeruginosa, Salmonella choleraesuis arizonae and Salmonella sp . The results showed that Fusarium. solani and Aspergillus niger had the highest antimicrobial effect against the gram negative bacilli bacteria, while their effect was less on the gram positive cocci bacteria ,in the contrast  Aspergillus terrrus and Penicillium chrysogenum were more effective against the gram positive cocci bacteria. Bacillus spp. had a wide broad spectrum effect on the pathogenic bacteria as most the isolates of Bacilus mgaterium and Bacillus licheniformis  had a broad spectrum effect on gram-negative and gram-positive bacteria because of their ability to produce antibacterial substances in varying proportions. However the isolates of  Bacillus Firmus, Bacillus pumilus and Bacillus sphaericus had a high effect against the gram negative bacteria while their antibacterial effect on Staphylococcus aureus was extremely limited. The antimicrobial substances of the most effective microbes were extracted using the organic solvent after fermentation of fungi and bacterial culture and then the antimicrobial activity of the extracted compounds was tested against the pathogenic bacteria.